A Quantitative Analysis of Memantine in Human Plasma Using Ultra Performance Liquid Chromatography/Tandem Mass Spectrometry. Issue 4 (2009) - Dubey, Sunil K.; Patni, Anil; Khuroo, Arshad; Thudi, Nageshwar R.; Reyar, Simrit; Kumar, Arun; Tomar, Manoj S.; Jain, Rakesh; Kumar, Nand; Monif, Tausif
Abstract : The aim of this study is to compare the single-dose oral bioavailability of memantine hydrochloride 10 mg tablets of Ranbaxy Laboratories Limited, with NAMENDA™ tablets (containing memantine hydrochloride 10 mg) of Forest Pharmaceuticals Inc. in healthy, adult, human subjects under fasting condition. The study was carried out as 2-way crossover design on 8 subjects in fasting and fed conditions. The plasma samples were obtained over a 72 h post dose in each period. Plasma memantine samples were analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) with positive ion electro spray ionization using multiple reactions monitoring (MRM). A sensitive, reproducible, accurate and validated LC-MS/MS method with limit of quantification (LOQ) 0.200 ng/mL was used to analyze memantine. Ln transformed AUC0-72 and Cmax were assessed for bioequivalence using 90% confidence interval (CI). 90% confidence intervals for the ratio of test and reference (Ratio of least-squares mean) for ln-transformed AUC0-72 and Cmax were within the regulatory acceptance criteria of 80-125%.